Faktor-faktor yang Menghambat Upaya Pemerintah dalam Merevitalisasi Sungai Cikapundung Kota Bandung - Christiady, Gantira; Mussadun, Mussadun (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2014)
Cikapundung has a huge tourism and mass transportation potency. it needs an revitalization effort to realize the waterfront city concept. The obstacle factors are 0.813 of economic factor, 0.805 of government policy factor, 0.748 of environmental factor, 0.716 of physic area factor, and 0.097 of social community factor. The constraints occur due to a lack of synchronization of the role and function of each stakeholder and the lack of incentives and disincentives are mutually beneficial for them. Some of recommendations that being made are Cikapundung people are expected to keep and maintain their neighborhoods and participate in plan activities by government actively, the private sector are also expected to participate in the development area, the government need an integrated grand design planning and provide limits building permit, and the researcher if they want to do further research related Cikapunung.